Optical and luminescence properties of Pr3+ in Gd2O3-CaO-SiO2-B2O3 glasses - Kaewjaeng S. (2017)
© 2016 Trans Tech Publications, Switzerland. This paper reports on the results concerning optical absorption and luminescence properties of 25Gd 2 O 3 -10CaO-10SiO 2 -(55-x) B 2 O 3 -xPr 2 O 3 (where x is 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 mol %) have been synthesized by melting and quenching process. The locations of the absorption peak observed are investigated for the first time. It is shown that the f-f transitions in the studied glasses are allowed by distortions of Pr 3+ ions. Seven absorption bands corresponding to the 3 H 4 → 3 P 2 , 1 I 6 + 3 P 1 , 1 D 2 , 1 G 4 , 3 F 4 , 3 F 3 and 3 F 2 , respectively absorption bands peaked at 459,483,575,1011,1418,1513 and 1931 nm. The luminescence intensity of Pr 3+ doped glass under excited at 459 and 483 nm, the emission band under excited at 459 nm wavelengths emission centered at 542 nm ( 3 P 0 → 3 H 5 ), 602 nm ( 1 D2→ 3 H 4 ), 646 nm ( 3 P 0 → 3 F 2 ) and 689 nm ( 1 D 2 → 3 H 5 ).The emission bands with 483 nm excitation wavelength, the emission band centered at 532 nm ( 3 P 1 → 3 H 5 ), 602 nm ( 1 D 2 → 3 H 4 ), 646 nm ( 3 P 0 → 3 F 2 ) and 725 nm ( 3 P 0 → 3 F 4 ), respectively. The present paper brings out the results pertaining to the studies carried out on different structural and optical absorption in UV-VIS-NIR region are also measured and discussed in term of energy levels, energy band gap and emission spectra of Pr 3+ ions doped in Gd 2 O 3 -CaO-SiO 2 -B 2 O 3 glasses.